Soil-transmitted helminth infections among preschool- and school-aged children in India: A systematic review and meta-analysis of prevalence, risk factors and intervention strategies - Chimdi Muoghalu; Sarah Lebu; Herbert Kaboggoza; Felix Bongomin; Stephen Ochaya; Musa Manga (Hygiene and Environmental Health Advances)
Soil-transmitted helminth (STH) infections are widespread in India, particularly among preschool- and school-aged children (PSAC and SAC). Following PRISMA guidelines, our study systematically garnered and synthesized existing literature to provide a comprehensive review and meta-analysis of STH infections among PSAC and SAC in India. We searched four databases - PubMed, Scopus, CINAHL, and Embase - and conducted a random-effects meta-analysis to estimate STH prevalence and assess risk factors. Additionally, we assessed the odds ratios for STH infections across various risk factors. From the 36 eligible articles, the pooled prevalence of STH infections was 27 % (95 % CI 19–36 %), with roundworm being the most common - 34 % (95 % CI 26 - 42 %). Our study results indicate that boys have higher odds of STH infections compared to girls (OR 1.29, 95 % CI 1.01–1.64), and maintaining good personal hygiene, such as regular handwashing, correlates with lower odds of STH infections (OR 0.36, 95 % CI 0.11–1.14). Current mitigation strategies in India include targeted deworming, mass drug administration (MDA), and water sanitation and hygiene (WASH) interventions. Targeted deworming faces challenges as dewormed school children may get reinfected by adults and untreated children. MDA requires substantial resource mobilization while deeply entrenched cultural norms constrain WASH interventions. These limitations highlight the need to explore innovative strategies for sustainable solutions to the issue of STH infections in India. To reduce prevalence, we recommend preventive chemotherapy alongside context-specific improvements in WASH conditions, complemented by strategic information, communication efforts, and effective policies.